Volunteering, Charitable Donation, and Psychological Well-Being of College Students in China - Geng, Yun; Chen, Yafan; Huang, Chienchung; Tan, Yuanfa; Zhang, Congcong; Zhu, Shaoming (Frontiers in Psychology, 2022)
Psychological well-being indicates individuals’ positive psychological functioning and well-being. A growing body of literature, largely based on adults and old people, suggests that volunteering and charitable donations are related to individuals’ psychological well-being. As emerging adulthood is a vital time for lifespan development, the aim of this study is to examine the effects of volunteering and charitable donation on individuals’ psychological well-being on college students. Relying on theories of altruism and the warm-glow theory, this study estimates the relationships among hours of volunteering, amount of charitable donations, and psychological well-being from 1,871 Chinese college students. The linear regression results indicate that students’ hours of volunteering and the amount of charitable donations in the past year were positively associated with their psychological well-being. Volunteering, compared to charitable donations, had a slightly stronger association with psychological well-being. This study provides a rationale for academic institutions to integrate social service activities into the curriculum as a potential tool to promote students’ psychological well-being.